The Relationship Between Visual and Auditory Cue Utilization. (November 2019) - Auton, Jaime C.; Wiggins, Mark W.; Sturman, Daniel
Within high-risk operational environments, expertise has typically been associated with a greater capacity to extract and utilize task-relevant visual cues during situation assessment. However, a limitation of this literature is its exclusive focus on operators' use of visual cues, even though cues from other modalities (such as auditory cues) are frequently engaged during this assessment process. Arguably, if the capacity for cue utilization is an underlying skill, those operators who have a greater capacity to use visual cues would also have developed a more nuanced repertoire of non-visual cues. Within the context of electricity distribution control, the current study recruited network operators ( N =89) from twelve Australian Distributed Network Service Providers. Using an online experimental platform, participants' visual cue utilization was assessed using an online situational judgement test (EXPERTise 2.0). Participants also completed the Auditory Readback Task which assessed their capacity to utilize various auditory cues (namely, final rising intonation, fillers, readback accuracy) when recognising nonunderstandings. The results showed a partial relationship between operator capacity for visual and auditory cue utilization. The outcomes of the current research have practical implications for the design of cue-based training interventions to increase the recognition of communication-related errors within distributed environments.